2007
DOI: 10.1038/sj.eye.6703006
|View full text |Cite
|
Sign up to set email alerts
|

Variation of blood pressure during topical phacoemulsification

Abstract: Background The changes of blood pressure in patients undergoing cataract procedure are not well studied. The blood pressures of cataract patients often become uncontrolled intraoperatively causing the procedure to be postponed. Intraoperative rise in blood pressure has been associated with ocular complications such as suprachoroidal haemorrhage and can be fatal from stroke or even myocardial infarction. We attempt to study the changes in blood pressure of patients undergoing cataract surgery. Aim Prospective s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
2
5
0
Order By: Relevance
“…[1][2][3] A perioperative rise in blood pressure (BP) has been noted during cataract surgery. [4][5][6][7][8] In fact, the guidelines from the American Academy of Ophthalmology suggest that BP monitoring should be performed during cataract surgery by personnel, other than the operating ophthalmologist, who is qualified to monitor and manage the patient's systemic status. 9,10 In addition to the intraoperative BP rise, intravitreal anti-VEGF injections have been demonstrated to increase the lifelong risk of cardiovascular and cerebrovascular events.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] A perioperative rise in blood pressure (BP) has been noted during cataract surgery. [4][5][6][7][8] In fact, the guidelines from the American Academy of Ophthalmology suggest that BP monitoring should be performed during cataract surgery by personnel, other than the operating ophthalmologist, who is qualified to monitor and manage the patient's systemic status. 9,10 In addition to the intraoperative BP rise, intravitreal anti-VEGF injections have been demonstrated to increase the lifelong risk of cardiovascular and cerebrovascular events.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, though the only risk factor noted preoperatively was older age, there could have been an increase in patient's systemic blood pressure during surgery. Yap et al have previously shown that there is a significant rise in systolic blood pressure especially in females during topical phacoemulsification [6].…”
Section: Discussionmentioning
confidence: 99%
“…This contributed to the increasing popularity of TA for cataract surgery, together with the rapid postoperative recovery it warrants (34,35) and the good level of analgesia it provides (3,36). Nevertheless, cardiovascular instability and psychomotor agitation have been reported with TA (32,37,38) and in a previous randomized study patients significantly preferred PA over TA (14). Other studies that randomly compared PA and TA during cataract surgery reported a similar incidence of complications and suggest that TA may be preferable (17)(18)(19).…”
Section: Statisticsmentioning
confidence: 99%